A Construction Procurement Method to Achieve Sustainability in Modular Construction. (2016) - Molavi, Jeffrey; Barral, Drew L.
Abstract: Modular or prefabricated construction has gradually replacing the traditional on-site construction due to the benefits provided, notably faster time, reduced costs, better work quality, and less environmental impacts. Prefabricated construction guaranties more control over the quality of components and safety of the construction process. However, some other concerns such as design considerations and coordination of factory and on-site activities, may be easily undermined if an appropriate procurement method is not selected. In a precast concrete construction, for instance, precast members require highly skilled workers, more complex techniques, and a more complex design. Because the design professionals need to concentrate on perfecting the modular design, the intensive administrative work may be neglected. To include these managerial task in a modular construction's equation, this study presents a fundamental understanding of modular and/or pre-fabricated systems and suggests a construction procurement method based on project type to satisfy this short coming and to achieve sustainable modular construction.